(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Restoration of blue carbon ecosystems, such as mangroves, is increasingly being used as a management for climate change mitigation by removing and sequestering carbon in the atmosphere. Mangrove rehabilitation activity held by the National Park since 2005, is one of the efforts to reduce green house gas (GHG) emissions. However, the growth and distribution of mangroves are non-optimal due to unfavorable environmental conditions. This certainly has an impact on the amount of carbon stock stored in mangroves. Therefore, this research aims 1) to estimate the potential carbon stock in restored mangroves on above ground (ABG), below ground (BGB), and soil carbon, and 2) to estimate the economic valuation of mangrove services as carbon storage. We calculate the carbon stock in ABG and BGB mangrove using a non-destructive method (allometric formula), while the calculation of soil carbon is carried out by analyzing the C-Organic content using mangrove rehabilitation (ABG+BGB+soil carbon) is 634.54 tonC/ha and CO2 sequestration is 2328.75 tCO2/ha. The economic value of mangrove rehabilitation for environmental services in storing carbon reached 375,202,308 IDR for the voluntary market and 980,528,697 IDR for the regulatory compliance (Clean Development Mechanism). The results can be used as initial information on mangrove ecosystem management policies, specifically as carbon storage for sustainable mangrove rehabilitation.